Ontario Human Rights Commission Right to Read Report: Sincere, Passionate, Flawed - Cummins, Jim (Journal of Teaching and Learning, 2022)
The Right to Read report highlights the fact that children who experience dyslexia are not being adequately supported in Ontario schools. The report’s call for the establishment of a more effective identification and intervention infrastructure within the school system is timely and persuasive. Unfortunately, the Right to Read report advances two unsubstantiated claims to explain the reading difficulties some children experience in the early grades. Specifically, it argues that Ontario schools are failing to teach reading skills effectively for all students, not just those with specific reading disabilities. Second, it attributes this general failure to the fact that most Ontario schools implement a balanced approach to reading instruction, which the report claims, pays insufficient attention to teaching sound/letter correspondences in a systematic, explicit, and intensive way. Neither of these claims is supported by the scientific data. Ontario students are consistently among the top performers in cross-Canada and international comparisons of reading performance. Furthermore, the empirical research is fully consistent with the implementation of a balanced or contextualized approach to literacy instruction that integrates the teaching of sound/symbol relationships with a more general commitment to immerse children into a literacy-rich instructional environment.